Growth Accounting for Saudi Arabia - Haque, Mohammad Imdadul (Asian Economic and Financial Review, 2019)
Saudi Arabia is a capital and energy-intensive economy and also dependent on expatriate labor. With the recent fall in oil prices, the Kingdom is actively pursuing structural transformation. The study identifies a research gap in estimating the contribution of labor and capital to the Saudi Arabian economy. This study focuses on estimating the relative contribution of major long-term determinants of economic growth. With the support of the auto-regressive distributed lag model (ARDL), the study establishes a co-integrating relationship between real gross domestic product (GDP), investment expenditure, labor force and education expenditure in Saudi Arabia. The study notices that the maximum contribution to real GDP growth in Saudi Arabia is from the labor force. The minimum contribution to real GDP growth comes from investments in the predominant oil sector. This study identifies the mechanisms to make the localization program successful. The study recommends further diversification in productive sectors to gain benefit from new investments and suggests cutting down the unproductive expenditure in education.